Analisis Penerapan Sistem Pengendalian Internal Dalam Mengelola Dana Desa (Studi Kasus Pada Desa Wolokoli Kecamatan Bola Kabupaten Sikka) - Maria Luciani Anryck Da Ona; Henrikus Herdi; Yoseph Darius Purnama Rangga (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze how the implementation of the internal control system in managing village funds in Wolokoli Village, Bola District, Sikka Regency based on Government Regulation Number 60 of 2008 and Domestic Manteri Regulation Number 20 of 2018.This research is qualitative research with descriptive analysis method.This research data was obtained from observations and direct interviews with related parties regarding the implementation of the internal control system in managing village funds in Wolokoli Village as well as documentation by providing information about the general description of Wolokoli Village, Vision and Mission of Wolokoli Village, Wolokoli Village Organizational Structure, Wolokoli Village Financial Statements and other documents related to research.The results showed that in Wolokoli Village in the process of managing village funds in theory has referred to the Manteri Regulation in the State Number 20 of 2018, but in practice there are still programs that have not been running or have not been realized because they are still constrained in the quality of human resources, so that the management of village funds in Wolokoli Village has not been fully independent.In addition, in the implementation of the internal control system in Wolokoli Village, there are also still several points that have not been implemented properly so that it seems not transparent.